Speed Bump Generator as A Power Source for Garden Lights - Prawira, Aditya; Purbolingga, Yoan (CHIPSET, 2026)
In an effort to explore environmentally friendly alternative energy solutions, this study develops a Speed Bump Generator system designed to generate electrical energy as a power source for garden lighting. The system harnesses the kinetic energy of vehicles passing over speed bumps and converts it into electrical energy, which is then stored in a battery. Experimental results indicate that the system is capable of producing an average current of 1.33 mA; however, the energy generated has not yet achieved the target storage capacity of 5 Ah. To improve system functionality, a Light Dependent Resistor (LDR) sensor is integrated to enable automatic lamp activation during nighttime conditions. The findings of this research provide a basis for further development toward more efficient and sustainable energy-saving lighting systems.